(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
This article is devoted to the essence of the work of Hayrat ul-abror, the first friend of Alisher Navoi’s "Khamsa". In the classical literature of the East, the tradition of Hamsa is well developed, and this is proved in the works of Navoi. The first epic of this quintet differs in the scope and structure of the theme.